(untitled) (LACCEI, 2024)
For a long time, the predominant paradigm in engineering has been inactive and discriminatory towards the needs of marginalized communities. However, there are a variety of proposals, practices and experiences that challenge this approach. Organizations in various parts of the world have developed proposals that value the social meaning of engineering and seek a new way of teaching and practice. Humanitarian engineering, peace-building engineering and popular engineering are some of the concepts that have been created and are grouped under the term Engaged Engineering. These new practices seek to transform the ethical foundations of hegemonic engineering and its relationship with nature, human beings and society. This approach is related to alternatives to development, such as Buen Vivir. This article analyzes and explains the characteristics of Engaged Engineering through the systematization of experiences, especially in development projects and educational approaches focused on social transformation. It also examines possible relationships between these engineering and the transition processes towards Buen Vivir in Latin America, in order to explore alternatives to the predominant paradigm in engineering.